VERMUNT’S LEARNING STYLES: SEARCHING FOR PORTUGUESE COLLEGE STUDENT’S FUNCTIONING - Rocha, Magda; Ventura, Marina (Journal of Learning Styles, 2011)
Abstract The current study addressed Vermunt´s model of learning styles (Vermunt, 1987, 1996, 1998, 2005) using the clusters methodological approach. A Portuguese higher education sample was analysed in order to build a comprehensive picture of its functioning. It was intended to determine if there were gender differences, age differences, as well as to see if there were relationships between learning styles, attending year, ,studies scientific area and age. 370 Portuguese university students, (male=119, female=251) coming mainly from the Catholic University of Portugal participated in the study. The sample was between 17 to 25 years (M=20.01; SD=1.61). All students were attending the first university education cycle (according to Bologna´s protocol). Respondents completed the Learning Styles Inventory (ILS, Vermunt, 1994) and a demographic questionnaire. Results are consistent with Vermunt‘s proposal. It was found an association between learning styles, scientific area and students‘ attending year. Results are discussed at theoretical and interventional angles. Estilos de aprendizagem de Vermunt: à procura do funcionamento dos estudantes portugueses no ensino superior Sumário Este estudo abordou o modelo de estilos de aprendizagem de Vermunt (Vermunt, 1987, 1996, 1998, 2005) utilizando a abordagem da construção de clusters. Analisou-se uma amostra portuguesa de alunos do ensino superior em ordem à construção de uma imagem compreensiva do seu funcionamento. Pretendeu-se estudar diferenças de género, bem como observar relações entre os estilos de aprendizagem, ano, área científica e idade dos alunos. 370 estudantes portugueses (homens=119, mulheres=251), maioritariamente da Universidade Católica de Portugal participaram no estudo. As idades variaram entre os 17 e os 25 anos (M=20.01; DP=1.61). Os participantes frequentavam o primeiro ciclo do ensino superior (segundo o protocolo de Bolonha). Os respondentes preencheram o Learning Styles Inventory (ILS, Vermunt, 1994) e um questionário demográfico. Os resultados são consistentes com a proposta de Vermunt. Encontraram-se associações entre estilos de aprendizagem, área científica e ano de frequência. Os resultados são discutidos à luz da teoria e da intervenção.
Keywords: Learning Styles; Portuguese Higher Education Students; Cluster Analysis; Demographic and contextual differences